Pengukuran Kualitas Layanan Website SMA Negeri 15 Surabaya Menggunakan Metode Webqual 4.0 Dan Importance Performance Analysis (IPA) - Afifah Pratiwi Reza Ayu Widiarti; Satrio Hadi Wijoyo; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
SMAN 15 Surabaya uses the website to disseminate information and news about the school to students. As one of the senior high schools that was included in the regional school category in Surabaya, it is important for SMA Negeri 15 Surabaya to provide qualified facilities as a form of quality assurance supervision. Thus, it is necessary to evaluate the quality of website service performance which until now has never been done. This assessment was carried out using the Webqual 4.0 and IPA methods. The results of testing on 107 students of SMA Negeri 15 Surabaya showed that there were 4 attributes with a high priority level of improvement, namely display attractiveness, timeliness, layout and format of information, and how easy it is to attract interest and attention. So that improvements will be focused on improving the appearance of the website and consistency in the delivery of information. Then there are 3 attributes with a low priority level of improvement, namely detailed information, relevance of information, and the ease of students in communicating with teachers. So that improvements are more focused on the content of information. While the other attributes have had good performance to excess so that it is sufficient to maintain the quality of its performance and does not require improvement. Recommendations for improvement given to attributes with high and low priority for improvement refer to research journals related to website interface design and appearance as well as HHS Web Usability Guidelines.